2018
DOI: 10.2139/ssrn.3291229
|View full text |Cite
|
Sign up to set email alerts
|

How Vulnerable Is Risk Aversion to Wealth, Health and Other Risks? An Empirical Analysis for Europe

Abstract: This paper empirically assesses how financial risk aversion reacts to a change in individuals' wealth and health and to the introduction of both financial and health risks using the Survey of Health, Ageing, and Retirement in Europe (SHARE). Individuals in our sample exhibit financial risk aversion decreasing both in wealth and health. Financial risk aversion is also found to increase in the presence of both background financial and health risks. Interestingly, the sensitivity of financial risk aversion to wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Instead, they may prefer solutions that they feel familiar with such as solutions which rely on nostalgic frames, even if these solutions are radical in practice. Related literature on risk aversion shows that individuals who are exposed to both economic and noneconomic risks are unwilling to make risky decisions (Courbage et al, 2018;Guiso and Paiella, 2008). Furthermore, Fernandez and Rodrik (1991) demonstrated that individuals favour the status quo over reforms when the distributive outcomes from these reforms are uncertain, even if these individuals are risk-neutral, forward-looking, and rational.…”
Section: Experience Of Status Decline and Expectation Of Status Declinementioning
confidence: 99%
“…Instead, they may prefer solutions that they feel familiar with such as solutions which rely on nostalgic frames, even if these solutions are radical in practice. Related literature on risk aversion shows that individuals who are exposed to both economic and noneconomic risks are unwilling to make risky decisions (Courbage et al, 2018;Guiso and Paiella, 2008). Furthermore, Fernandez and Rodrik (1991) demonstrated that individuals favour the status quo over reforms when the distributive outcomes from these reforms are uncertain, even if these individuals are risk-neutral, forward-looking, and rational.…”
Section: Experience Of Status Decline and Expectation Of Status Declinementioning
confidence: 99%
“…Decker and Schmitz (2016) find that a physical health shock (measured by a loss of grip strength) decreases one's willingness to take risks (WTR). Schurer (2015) finds a positive association between self-rated health and the WTR, which was confirmed more recently by Courbage et al (2017).…”
Section: Motivationmentioning
confidence: 59%
“…Step 6 We prove assertions (i)-(ii). We consider the PDEs (5.8) and (5.10) where we replace π * 0 with π 0 ∈ B.…”
Section: By Proposition 52 and Point 3 From Definition 41 We Note mentioning
confidence: 91%
“…However, many empirical studies suggest that agents' risk attitudes are correlated with their wealth, see e.g. Shaw [21], Wik et al [22], Anderson and Galinsky [1], Bucciol and Miniaci [5], Courbage et al [6]. Consequently, we should use wealthdependent risk aversion coefficients to model, and understand, economic decisions of investors and insurance companies in risky environment.…”
Section: Introductionmentioning
confidence: 99%